2011
DOI: 10.1111/j.1549-8719.2011.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation on a Large Scale: Techniques, Tactics and Relevance of Studying the Microcirculation in Larger Population Samples

Abstract: The role of microcirculatory dysfunction is increasingly being recognized in the etiopathogenesis of cardiovascular disease. Whilst the importance of detailed mechanistic studies to determine the exact nature of these disturbances is without question, it was large-scale population-based studies that first identified the associations between deranged microvascular perfusion, autoregulation or structure, and subsequent target organ damage. This is the subject of considerable studies to establish whether there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Third, these techniques are confounded by local neurohumoral influences, circulating substances, and paracrine or mechanical impact from underlying parenchymal cells. Moreover, most techniques require careful training and are costly, making it difficult to include measurements of microcirculatory function in large populations studies 67 . More recently three non-invasive methods have been validated to assess microvascular flow.…”
Section: Assessing Human Microcirculatory Functionmentioning
confidence: 99%
“…Third, these techniques are confounded by local neurohumoral influences, circulating substances, and paracrine or mechanical impact from underlying parenchymal cells. Moreover, most techniques require careful training and are costly, making it difficult to include measurements of microcirculatory function in large populations studies 67 . More recently three non-invasive methods have been validated to assess microvascular flow.…”
Section: Assessing Human Microcirculatory Functionmentioning
confidence: 99%
“…These data strengthen the possibility of using retinal imaging as a clinical tool for diagnosing microvascular disease. 42 Finally, narrow arterioles had no effect on all-cause mortality. All reported deaths were similarly distributed between the groups.…”
mentioning
confidence: 97%
“…3,21,22 Hypertensive retinopathy was first described in the 19th century and has been used since then in the diagnosis of the severity of hypertensioninduced target organ damage. However, the classic assessment of retinopathy was descriptive and gave no quantitative or mechanistic data on the microcirculatory dysfunction.…”
Section: Retinal Imagingmentioning
confidence: 99%
“…Large-scale epidemiological studies in the last 2 decades have identified the associations among deranged microvascular perfusion, structure, target organ damage, and subsequent cardiovascular disease. 3 Major technological developments now allow study of the microcirculation both in mechanistic and epidemiological studies. The purpose of this Brief Review is to provide a critical appraisal of these developments and their particular impact on hypertension research.…”
mentioning
confidence: 99%